Konsep Hukuman Menurut John Austin - Depi Novianti; Wildan Nuari; Fitriyani, Dewi; Pikri Pirdaus; Febri Rizki Amelia; Irfan Ruli Adriansyah (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
Anyone who violates the law must be punished according to what he did, the purpose of the punishment is to deter the perpetrators. The purpose of this study is to examine the notion of punishment in general and in particular according to John Austin as an important figure in the field of law. The research method used is qualitative, where the type of library research is carried out through a normative research approach and legal philosophy. The justification of legal theory of legal positivism is that orders issued by the rulers of law are orders of parliament, ie. order of the highest authority or holder of sovereignty. Every member of society must comply with these rules, and those who break them will be subject to severe and real sanctions. According to John Austin, sanctions are an important part of law and part of orders because sanctions are the result of not obeying his orders, meaning that the orders in question contain sanctions. Sanctions in general are punishments, but according to John Austin, these punishments are part of the sanctions. According to Austin, sanctions are one of the most important elements of law, sanctions must also be made in the spirit of Austin’s orders, in the sense that they are included in sanctions or compliance (enforce obedience), which in a sense. duties or responsibilities and understanding of assigned (higher and lower) government mandates. The sanctions imposed by Austin are intrinsically related to orders because they are the result of disobedience to orders. Someone often understands sanctions as punishment (punishment). However, according to Austin, sentencing is only part of the sanctions and is considered too narrow to equate punishment with punishment.